The association between mortality and use of Chinese herbal medicine among incident stage IV esophageal cancer patients: A retrospective cohort study with core herbs exploration - Chen, Shu-Ling; Lin, Wei-Chun; Chen, Yu-Chun; Chen, Jiun-Liang; Wu, Yi-Hong; Yang, Sien-Hung; Chen, Hsing-Yu (Frontiers in Pharmacology, 2022)
Esophageal cancer (EC) remains a leading cause of death worldwide and in Taiwan. The prognosis of advanced-stage EC is notably poor, and the treatment options are limited. Chinese herbal medicine (CHM) has been widely used as a complementary treatment for cancer, yet the long-term effect of CHM in stage IV EC remains unclear. The multi-institutional cohort obtained from the Chang Gung research database (CGRD) was used to study the long-term outcome of CHM use among incident stage IV EC patients from January 1, 2002, to December 31, 2018. All patients were followed up to 5 years or the occurrence of death. The overall survival (OS) and disease-specific survival rates were conducted using Kaplan-Meier estimation. Overlap weighing and landmark analysis were used to eliminate confounding and immortal time biases. Furthermore, we demonstrated the core CHMs for stage IV EC by using the Chinese herbal medicine network (CMN) analysis on prescriptions. Nine hundred eighty-five stage IV EC patients were analyzed, including 74 CHM users and 911 non-CHM users. We found the use of CHM was associated with a higher 5-year overall survival rate than CHM nonusers (the cumulative probability: 19.52% versus 6.04%, log-rank test: P < 0.001, and the P < 0.001 with overlap weighting). In addition, the overall median survival time was about seven months longer among CHM users. Moreover, the lower 1-, 3-, 5-year disease-specific survival rates were higher among CHM users. Additionally, the risk of all-cause mortality was lower among CHM users when considering accessible demographic covariates (adjusted hazard ratio: 0.59, 95%CI: 0.39, 0.89, P=0.011). Furthermore, the CMN analysis revealed that CHMs improved health while relieving tumor burden. For example, Hedyotis diffusa Willd. was the core CHM with an anti-cancer effect, while Fritillaria thunbergii Miq and Sevilla maindronide Rochebrune were used together to relieve cancer-related gastrointestinal discomfort. The use of CHM seems safe and possibly beneficial among stage IV EC patients with a higher 5-year OS. Further clinical trials on CHM were guaranteed to explore the role of CHM in managing stage IV EC patients.